Corporate social responsibilities practices in Brazilian context: an analysis of business model for sustainability and best place to work - Campos, Simone Alves Pacheco de; de Andrade, Taís; Estivalete, Vania de Fátima Barros; Costa, Vivian Flores; Stefanan, Aline Armanini (Revista de Administração da UFSM, 2014)
This study aims to analyses the corporate social responsibility (CSR) and human resource management practices of organizations considered model in sustainability and are best places to work. Thus, we carried out a research by analyzing the Guides Exame de Sustentabilidade e Melhores Empresas para Trabalhar, comprising the period from 2006 to 2011. In relation to practices associated to social/cultural dimension of CSR, the results shows the concern with supporting education and local development. In relation to practices related to environmental/ecological dimension of CSR, there was a predominance of practices related to the use of recyclable materials. The human resource management practices prioritized traditional actions, with less concern with social, behavioral and ethical aspects. Even organizations investigated are model in HRM and CRS, were shown gaps related to the interaction of HRM practices with CSR internally.